THE DETECTION OF MYC PROTEINS IN THE DEVELOPING HUMAN KIDNEY - Erdösová, Běla; Wagner, Filip; Kylarová, Dana (Biomedical papers, 2004)
The aim of our work was the detection of c- and N- myc proteins in the developing kidney of human fetuses especially in the neogenous zone. These proteins being localized in nucleus and encoded by the cellullar oncogene myc function as transcriptional factors. Myc gene represents the key control gene in the course of cellular proliferation and differentiation. It also participates in the regulation of apoptosis and the origin of some cancers. Both proteins have been proved to be inevitable for proper nephrogenesis in mice. Considering the dearth of studies dealing with human embryonic tissues, we attempted to map the localization and spatiotemporal relations of the expression of these proteins during human nephrogenesis. In addition, issuing from our previous observations, we tried to compare their ways of expression with those of Bcl-2 (antiapoptotic effect) and Bax (proapoptotic function) proteins. Histologically normal kidneys were collected from eight human fetuses ranging from the 10th- 30th week of IUD. Tissue samples were fixed in methacarn and processed by routine paraffin technique. Standard indirect three-step immunohistochemical method was applied for the detection of N- and c-myc proteins. In the neogenous zone both proteins are markedly present in metanephrogenic blastema with declining intensity with the increasing age of fetus. Branches of ureteral bud are almost negative. Such localization is also typical for Bcl-2 protein whereas Bax positive cells are present mostly in branches of the ureteral bud. It is not clear if all these proteins collaborate in the course of regulation of apoptosis in human metanephros.
Keywords: Myc family/C-myc/N-myc/Apoptosis/Nephrogenesis/Bcl-2 family